IMPLEMENTASI PEMBERIAN NAFKAH ANAK PASCA PERCERAIAN DI PENGADILAN AGAMA SURABAYA STUDI PUTUSAN NOMOR 2669/PDT.G/2023 P.A SBY - Intan puspita sari; Hariyo Sulistiyantoro (Civilia: Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2023)
This research was motivated by the father's negligence regarding his child support obligations after divorce. According to the Al-Quran, Hadith, Marriage Law and the Compilation of Islamic Law (KHI), child support is the father's obligation. Divorce does not eliminate the father's obligation to support his children. The problem raised in this research is how to pay child support after divorce. Because children need to be protected and treated in a civilized manner. The aim of this article is to understand what happens if a court decision is not implemented voluntarily and to find a solution so that the decision is not only a miscarriage of justice but can also guarantee justice and the practical benefits of the decision. Based on the author's analysis, it can be concluded that in the event that the decision regarding the ex-husband's obligations is not implemented voluntarily, you can try to submit a request to the Religious Court in Surabaya which will consider implementing the decision.